The marketing strategy for sugar palm (Arenga pinnata) by people around the protected forest aren HPHTI of Toba Pulp Lestari. Issue 1 (February 2020) - Azhar, I; Nasution, Z; Delvian; Agussabti; Riswan; Risnasari, I; Sembiring, M R; Sidabukke, S
Abstract: Sugar palm is a plant that produces various high economy value product. The superior products of sugar palm as a food and energy source, among others, are brown sugar, palm-suiker, fresh sap, kolang-kaling (a type of candied fruit made from palm sugar), and alcoholic beverages. The purpose of this study was to analyse the marketing strategies that can be adopted by the community who utilise sugar palm living around the area of PT. Toba Pulp Lestari. Analysis carried out in this study is analysis SWOT. The results of this study found that there are several strategies that have been made based on the SWOT analysis. One of them is creating farmer groups and cooperatives at the village level, providing market information to farmers, increasing road access, and developing farmer capacity building.